Stability and eco-friendly design of SWATH hulls for recreational use / Rosyimie Mohamad Shukri - Mohamad Shukri, Rosyimie (2025)
The stability and eco-friendly of hull designs are very important in improving marine engineering, especially for recreational boats where passenger comfort and the environment are the main concerns. This study focuses on changing a traditional monohull boat into a SWATH to solve problems of instability and inefficiency in recreational boating.